THE DEVELOPMENT OF THIRD-PARTY LOGISTICS' BUSINESS MODEL FRAMEWORK FOR SMALL CONTRACTORS IN BANDUNG RAYA - Shanti Cahyani S M, Fauziah
Small contractors' logistics challenges stem from financial and project cash flow constraints, which lead to inefficient supply chains and low bargaining power with suppliers. This study introduces a material logistics system for small contractors, which uses a third-party logistics (TPL) service provider as an intermediary between material suppliers and small contractors. Large-scale and complex projects in Europe have successfully implemented TPL logistics systems, which have a positive impact on project and logistics performance. It also reduces the environmental impact of construction logistics activities. This study addresses a research gap concerning TPL implementation in small-scale construction projects, an area that the construction industry has yet to embrace. The purpose of this research is to develop a TPL business model framework that can address the logistics challenges of small contractors. This research was conducted in stages according to each analysis theme, i.e., small contractor logistics practices (PL), potential entities as TPL business candidates (PE), and TPL’s business model framework (MB). This research adopted the TPL’s business model framework from the nine canvas blocks in the Business Model Canvas (BMC), i.e., customer segments (CS), value propositions (VP), channels (C), customer relationships (CR), revenue streams (R$), key activities (KA), key resources (KR), key partners (KP), and cost structure (C$). A new component, i.e., a service type (JL), was added to clarify the TPL services. This research employed a qualitative methodology, collecting data through semi-structured interviews with interviewees from small contractor companies in the Greater Bandung Area. This research also involved material suppliers and government representatives, i.e., Dinas PUPR and Disperindag, in focus group discussion (FGD) activities with the aim of exploring the potential entities to conduct TPL business. Content analysis and thematic analysis are the data analysis methods used in this study. Experts and practitioners in logistics and construction validated the research findings. According to the study of logistics practices (PL), small contractors faced challenges in logistics planning, procuring and purchasing materials, providing material storage at the project site, and timely material delivery. These results present an opportunity for TPL to act as a consolidator of material requirements from small contractors. These materials include reinforcing steel, cement, asphalt, bricks, sand, aggregate, and ready-mix concrete. The TPL will simplify the material sourcing process, provide temporary material storage services off-site, and ensure material delivery to construction sites. The study of potential entities as TPL business candidates (PE) shows that transportation service providers have greater potential than other entities to become TPL business actors, as they can perform material handling and material delivery. TPL's business model framework (MB) is defined in terms of business model components, i.e., CS, VP, JL, R$, C, CR, KA, KR, KP, and C$. Small contractors' capacity in the Greater Bandung Area represents a potential customer segment (CS) for TPL. TPL's value proposition (VP) is to guarantee the supply of materials to the project site. TPL differentiates its service type (JL) based on material characteristics. Type-1 services cater specifically to consolidated manufactured materials such as reinforcing steel, cement, asphalt, and bricks, offering sourcing, warehousing, and coordination services. Type-2 services specialize in sand and aggregate sourcing and delivery coordination. Type-3 services specialize in coordinating material sourcing for ready-mix concrete. These three services are the source of TPL's revenue stream (R$). Logistics technology must serve as a channel for TPL's services to distribute the value proposition to customers (C), with information systems supporting transactions and material delivery tracking. Personnel assistants can facilitate the customer relationship (CR) mechanism between TPL and small contractors. The VP, JL, C, and CR components generate the main activities (KA) in TPL's service system, namely the sourcing process, material storage management (warehousing), and material transportation (transporting). These activities require key resources (KR), namely human resources, logistics technology, vehicles, warehouses, and financial resources. TPL can meet these resources by collaborating with transportation service providers, warehousing facility providers, and material suppliers, who serve as its main partners (KP). TPL's cost structure includes labour costs, transportation costs, storage costs, technology development costs, and management costs. We can use the cost-plus-fee method, a dynamic pricing strategy, and activity-based costing (ABC) for cost modelling. Despite its limited sources and study areas, this research can still make a significant contribution if expanded to other areas, given the common characteristics of small contractors. TPL can tailor the variety of projects, materials, and services it offers to meet the needs of small contractors in its operating area. The TPL business model framework generated from this research is practical and applicable, with a research design structure that can facilitate practitioners and academics to conduct further review and development. All parties involved, including small contractors, material suppliers, and construction clients, anticipate benefits from TPL's involvement in supporting small contractors' supply chains. All parties involved must commit to their respective roles to achieve these benefits. The next study is to conduct a feasibility study of TPL's business model to improve its success in the construction supply chain.